Imaging Biomarkers in Prostate Stereotactic Body Radiotherapy: A Review and Clinical Trial Protocol - Liu, Wei; Loblaw, Andrew; Laidley, David; Fakir, Hatim; Mendez, Lucas; Davidson, Melanie; Kassam, Zahra; Lee, Ting-Yim; Ward, Aaron; Thiessen, Jonathan; Bayani, Jane; Conyngham, John; et al. (Frontiers in Oncology, 2022)
Advances in imaging have changed prostate radiotherapy through improved biochemical control from focal boost and improved detection of recurrence. These advances are reviewed in the context of prostate SBRT and the ARGOS/ CLIMBER trial protocol. ARGOS/ CLIMBER will evaluate (1) the safety and feasibility of SBRT with focal boost guided by mpMRI and 18F-PSMA-1007 PET (2) imaging and laboratory biomarkers for response to SBRT. To date, response to prostate SBRT is mostly commonly evaluated using the Phoenix Criteria for biochemical failure. Drawbacks of this approach include lack of lesion identification, a high false positive rate, and delay in identifying treatment failure. Patients in ARGOS/CLIMBER will receive dynamic 18F-PSMA-1007 PET and mpMRI prior to SBRT for treatment planning and at 6 months and 24 months after SBRT to assess response. Imaging findings will be correlated with PSA and biopsy results, with the goal of early, non-invasive, and accurate identification of treatment failure.